Milestone of the most used maximum power point tracking in solar harvesting system - Sutikno, Tole; Subrata, Arsyad Cahya; Jopri, Mohd Hatta (Institute of Advanced Engineering and Science (IAES), 2022)
Solar harvesting system with photovoltaic (PV) is one of the most desirable renewable energy sources because of its prominent advantages. However, low efficiency due to fluctuating output power is a major problem for PV systems. A technique used to maximize power extraction known as maximum power point tracking (MPPT) has been proposed by various literature to deal with this problem. One of the most widely developed MPPT methods due to its ease of implementation is perturb and observe (P&O). Since the initial discovery of the principle, the P&O method has been extensively modified including the fixed step-size: step-size variables, partial shading, threshold module current, three-point-comparison, maximization of dynamic performance, minimization of dynamic performance, bandwidth of